Design of a Point of Sales and Membership Integration Model at Campus Business Unit in Politeknik Negeri Manado - Paendong, Melky; Kumaat, Arief Perdana; Mandulangi, Jufrina; Artana, I Made Wahyu (Asian Journal of Logistics Management, 2024)
Campus business units have great potential to become innovative business laboratories.  By adopting advanced information technology, campus business units can develop unique business models that are relevant to market needs. Therefore, there is a need for innovation and business strategies that enable to compete with similar business. One strategy that can be implemented is to integrate the product database with the creation of a membership program for customers.This research employs a prototyping approach for system development. This method divides the system into several stages that are directly implemented as models. The prototype is designed through use case diagram and activity diagram of each actor that involved in the process.As a result, a proposed design is able to control 6 control components, namely: Business Unit Admin, UPT Admin, Cashier, Shopkeeper, and Customer. On the other hand, the integration between the Point of Sales System and Membership can be seen in the key activities of customers and cashiers, where both parties will collaborate in controlling the transaction status, showing availability of special offers for members in the form of points or discounts, and calculating the appropriate offers for the completed transactions.